Should countries promote foreign direct investment? - Hanson, Gordon H. (UN New YorkUS, 2001)
Examines whether policies to promote foreign direct investment (FDI) make economic sense. Focuses on whether existing academic research suggests that the benefits of FDI are sufficient to justify the kind of policy interventions seen in practice.